Money as God?: The Monetization of the Market and its Impact on Religion, Politics, Law and Ethics - Hagen, Jürgen von; Welker, Michael (EBL-Schweitzer, 2014)
Cover; Half-title page; Title page; Copyright page; Contents; Figures; Tables; Contributors; Acknowledgments; Introduction; I Money and markets: economic, legal, and theological foundations; 1Microfoundations of the uses of money; 2Money and its role in a decentralized market economy; 3 Mensura et mensuratum:money as measure and measure for money; 4 Standardization and monetization: legal perspectives; 5Kohelet and the co-evolution of a monetary economy and religion; II Monetary exchange: historical and social roots; 6 Money and image: the presence of the state on the routes of economy